PENGELOLAAN PEMBELAJARAN PKN MELALUI PENERAPAN TEKNIK SKEMA - Wita Mahdalena (UNIVERSITAS BENGKULU, 2015)
Class Action Research aims to describe the learning management Civics through the implementation of the scheme engineering students at SMK 2 Bengkulu City . This study was conducted on 30 students of class 2. Data collected malalui observation of teachers , students and study notes . The results showed the average value before the action research by 50 % , and the average value of 73% after the action . This shows an increase in students' understanding of civics at 23 %.Keywords: learning management , engineering scheme